Dataset on Systematic Literature in Digital Marketing Communication Research within 2020-2022 - Daniel Susilo (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
This study provides a thorough summary of a dataset that was built from systematic literature reviews undertaken between the years 2020 and 2022. The dataset presented in this study comprises a comprehensive collection of research studies pertaining to the domain of digital marketing communication, sourced from the SCOPUS Database. The utilisation of a systematic approach guarantees a comprehensive compilation, examination, and integration of pertinent scholarly publications, providing a unified perspective on the developing patterns, principal themes, approaches, and discoveries within this ever-evolving field. The dataset has been carefully curated to encompass a wide range of subjects that have been investigated in research on digital marketing communication throughout the designated timeframe. The dataset encompasses a range of topics that reflect the dynamic nature of digital marketing techniques, including the assessment of the effectiveness of social media advertising and influencer marketing, the exploration of the consequences of AI-driven customisation, and the examination of concerns related to data protection. In addition, the dataset brings attention to methodological intricacies, providing insight into the current research methodology, data sources, and analytical tools used to enhance knowledge in this field. The dataset is a helpful resource for scholars, practitioners, and policymakers who wish to understand the intricacies and advancements in digital marketing communication within the specified time frame. It offers a systematic collection of insights. This abstract highlights the dataset's significance in advancing knowledge, guiding strategic decision-making, and stimulating further research in the dynamic field of digital marketing communication.